The Concept of Value for Money In Measuring Financial Performance at Dadi Keluarga General Hospital - Lita Hervitasari (JASS (Journal of Accounting for Sustainable Society), 2024)
AbstractHospitals play a crucial role in providing quality healthcare services to the community while ensuring operational sustainability through sound financial management. The concept of Value for Money (VfM) becomes highly relevant in hospital financial management as it emphasizes three key elements: economy, efficiency, and effectiveness. This study examines the application of VfM in evaluating the financial performance of Dadi Keluarga General Hospital, Ciamis, during the 2018–2023 period. The analysis focuses on assessing whether the hospital's financial management strategies align with VfM principles.The findings reveal varied results across the three VfM dimensions. In terms of economy, the hospital generally achieved economical performance with an average economy ratio above 90%, except in 2020, where the ratio exceeded 100%, indicating uneconomical spending due to budget overruns. In terms of efficiency, most years showed efficient performance with ratios below 100%, except in 2020, when inefficiency occurred with a ratio of 103%. For effectiveness, the results were more fluctuating; the hospital achieved effectiveness in 2019 (107%) and 2021 (114%), but failed to meet targets in other years due to unrealized revenue.The study concludes that while Dadi Keluarga General Hospital has implemented VfM principles, their application remains inconsistent and requires further improvement. To optimize VfM implementation, the hospital needs to enhance strategic planning, budget management, and periodic performance evaluation. These efforts will support financial sustainability while improving accountability and transparency in public sector financial management. This research contributes both academically and practically to advancing VfM-based performance measurement in healthcare institutions.